Babak Baru Nuklir Iran: Memahami Manuver Iran dan Dinamika Politik Kawasan Timur Tengah - Rofii, Muhammad Sya'roni (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2015)
Nuclear deal between Iran and the West has recently brought a significant impact on changing political map of the Middle East region. Many parties assumed that the nuclear agreement initiated by the United States is part of the scenario to keep the Middle East remained stable. For the past five years America was so overwhelmed in facing threats either by state actors or non-state. At least with the achievement of the Iranian nuclear deal America can be free from a potential direct threat of nuclear weapons. However, this step is not fully run smoothly because the negotiation was challenged by the US strategic ally, Saudi Arabia and Israel, both criticized the policy of the White House as an error. Behind security considerations, economic factor also played significant role in sealing the deal. What are the main reasons and dynamics behind the deal? This paper intends to review these dynamics by elaborating prominent reports and research findings.